Solid-Liquid Phase Transfer Catalyzed Selective Reduction of Bifunctional Moieties - Verma, Monika; Sharma, Renu; Bharti, Ruchi (Orbital: The Electronic Journal of Chemistry, 2021)
In this article, a chemoselective reduction process of various aldehydes to their corresponding alcohols is described. An aqueous solution of various aromatic and allylic aldehydes was treated with NaBH4 and tetrabutylammonium iodide as a phase transfer catalyst by choosing appropriate concentrations to give their respective alcohols in good to moderate yield. This methodology offered several advantages, including simple environmentally benign experimental procedure, good yields, short reaction time, and no toxic by-product.DOI: http://dx.doi.org/10.17807/orbital.v13i4.1576